2015
DOI: 10.1155/2015/137357
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Periodontal Infection and Its Putative Links with Alzheimer’s Disease

Abstract: Periodontal disease (PD) and Alzheimer's disease (AD) are inflammatory conditions affecting the global adult population. In the pathogenesis of PD, subgingival complex bacterial biofilm induces inflammation that leads to connective tissue degradation and alveolar bone resorption around the teeth. In health, junctional epithelium seals the gingiva to the tooth enamel, thus preventing bacteria from entering the gingivae. Chronic PD involves major pathogens (Porphyromonas gingivalis, Treponema denticola, and Tann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 127 publications
(163 reference statements)
3
151
0
13
Order By: Relevance
“…Periodontal disease is a prevalent chronic inflammatory disease of the oral cavity which is the major cause of tooth loss in adults [27]. Almost all forms of periodontal disease occur due to mixed microbial infections and many bacterial species are recognized as putative periodontal pathogens, such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Bacteroides forsythus, Prevotella intermedia, Peptostreptococcus micros, Fusobacterium nucleatum, Filifactor alocis, Desulfobulbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal disease is a prevalent chronic inflammatory disease of the oral cavity which is the major cause of tooth loss in adults [27]. Almost all forms of periodontal disease occur due to mixed microbial infections and many bacterial species are recognized as putative periodontal pathogens, such as Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Bacteroides forsythus, Prevotella intermedia, Peptostreptococcus micros, Fusobacterium nucleatum, Filifactor alocis, Desulfobulbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial and immune dysbiosis, which it creates, occurs despite the fact that P. gingivalis is often only present in low numbers in diseased sites. Although the subversive effects of P. gingivalis mostly have been related to innate immunity (2, 7, 13), which is the host’s first defense met by microbial pathogens, it also has several ways to subvert the adaptive immune response within the periodontium (Table 1). Arteries and the demented brain also suffer the effects of P. gingivalis oral infection, albeit subtly, in the brain compared with atherosclerosis.…”
Section: P Gingivalismentioning
confidence: 99%
“…An international team recently urged that cerebral pathogenic infections by herpes simplex virus type 1 (HSV-1), C. pneumoniae , spirochetes, and fungi be considered as candidate AD initiators (Itzhaki et al, 2016). Similarly, extracerebral infectious pathogens were also considered as AD triggers; for example, oral pathogenic infections by the periodontal bacteria Porphyromonas gingivalis and Actinomyces naeslundii were identified as high-risk factors driving development toward AD (Noble et al, 2014; Singhrao et al, 2015). A recent study on gut microbiota dysbiosis indicated that intestinal microbiome alterations are related to the malfunctional motor phenotypes, suggesting the overgrowth of intestinal commensal microbes (i.e., opportunistic infection) acting as a neurodegenerative driver (Scheperjans et al, 2015).…”
Section: Biotic Stress and Admentioning
confidence: 99%